Review of the genus Synochoneura Obraztsov, with the description of a new species from China (Lepidoptera: Tortricidae) - Wang, Xinpu; Li, Houhun (Zootaxa, 2007)
Synochoneura is a small genus restricted to China. The genus is reviewed, and one new species is described: Synochoneura dentana sp. n. The female of S. tapaishani (Caradja) is reported for the first time. Images of adults, male genitalia, and female genitalia are provided, along with a key to the known species.